AI-Powered User Experience and Interactions with Galleries, Libraries, Archives and Museum (GLAM) - Di Marzo Serugendo, Giovanna; Friha, Lamia (Revue électronique suisse de science de l'information (RESSI), 2025)
The integration of Artificial Intelligence (AI) techniques, including machine learning, knowledge engineering, autonomous intelligent agents, distributed AI, Natural Language Processing (NLP), and generative AI, is set to transform human-machine interactions. In parallel, advancements in User eXperience (UX) research, particularly in Virtual and Augmented Reality (VR/AR), or holographic interfaces, are enabling more intuitive and effective ways to engage with digital systems. This paper explores the transformative potential of the joint use of these technologies in the context of libraries and the broader GLAM (Galleries, Libraries, Archives, and Museums) sector. This paper discusses these innovations alongside real-world use cases from the GLAM sector, currently being developed at the University of Geneva. They illustrate how AI-powered solutions combined with UX techniques are reshaping the way we interact with cultural and scientific knowledge, making it more accessible, engaging, and impactful for diverse audiences.